Administration of post-reformation decentralization government - Umar, Akmal; Nur Naninsih, Umi Farida,; Sahabuddin, Chuduriah (Opción, 2019)
The study aims to investigate administration of post-reformation decentralization government implemented in the city of Makassar. The method used is a literature study, in addition, the authors also use media such as newspapers, magazines, bulletins, and other sources relating to the discussion as reference material in reviewing the discussion, analysis using descriptive-analytic methods. As a result, the implementation of decentralization that has been running is growing the regional economy of each district/city. In conclusion, urban space that allows the division of regions for development will be easier, and more perfect to become a municipality